The deafferented nonhuman primate is not a reliable model of intractable pain - Pioli, Elsa Y.; Gross, Christian E.; Meissner, Wassilios; Bioulac, Bernard H.; Bezard, Erwan (Neurological research (New York), 2003)
Before extending the application of motor cortex stimulation it is important to investigate the intimate mechanisms by which it alleviates intractable pain and to consider possible side effects. Self-mutilation in animals following extensive neurectomy or posterior rhizotomy of a limb is thought to reveal severe dysesthesias in the deafferented zone suggesting its usefulness as an animal model of chronic pain in humans. We here show in deafferented nonhuman primates that the autotomy behavior immediately follows the surgery and disappears after 28 days. In keeping with the experience of Y. Lamarre, the simple but careful care of all wounds is sufficient to abolish this behavior. Our results do not exclude the possibility that the deafferentation is still painful for the monkeys, but they definitely rule out that autotomy is a consistent response to deafferentation.